Indonesia Analysis of the Practicality of Booklet According to Educators and Students in Learning Process - Zulyusri; Oktavia, Fifi (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
In an effort to create the expected learning process, educators need to package and improve the attractiveness of learning media so that students like it. The selection of appropriate media has a very significant impact on the level of motivation of students to learn. Booklets are one type of learning media that can be suitable for use in learning. The existence of this booklet has been proven to support the teacher's role as an information provider for students, and can increase students' interest in learning. This study aims to evaluate the practicality of using booklets in learning. The method used in this research is meta-analysis. The data used in this study are secondary data obtained from scientific publication articles. Based on the results of the study, the average practicality of booklets according to educators' responses to learning booklets from the articles analyzed was 89.77%, which indicated a very practical category. Meanwhile, according to students' responses, the practicality of using the booklet is 89.15% with a very practical category. The results of the meta-analysis concluded that the use of booklets in learning proved to be very practical according to the assessments of both educators and students. This indicates that the developed booklet is able to provide assistance and convenience in the learning process for educators and students. Keywords: Meta-analysis, Booklet, Practicality